Treatment of Skin Scar Using CO2 Laser with or Without Corticosteroid - Al Ani, Salih A.; Awazli, Lutfi G. (Iraqi Journal of Laser, 2019)
CO2 Laser (10600nm) is the recent method in the management of challenging skin scar resulting from trauma, burn and surgical wound. The aim of this study was to evaluate the efficacy & safety of fractional CO2 laser (10600nm) in treatment of skin scar. Materials and Methods:Twenty patients with different types of scars treated with fractional CO2 (10600nm) laser, (10 patients) were given additional intralesional Triamcinolone. Results: All of the twenty patients included in this study showed some sort of improvements in scar texture, height and pliability and all of the ten patients who received intralesional Triamcinolone after laser show complete satisfaction. Conclusion:Fractional CO2 (10600nm) laser can be used as alternative, effective, safe and less side effects method to other conventional method in treatment of scar specially when combined with intralesional Triamcinolone.